Contextual Sentence Similarity from News Articles - Chaturvedi, Nikhil; Dubey, Jigyasu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
An important topic in the field of natural language processing is the measurement of sentence similarity. It’s important to precisely gauge how similar two sentences are. Existing methods for determining sentence similarity challenge two problems Because sentence level semantics are not explicitly modelled at training, labelled datasets are typically small, making them insufficient for training supervised neural models; and there is a training-test gap for unsupervised language modelling (LM) based models to compute semantic scores between sentences. As a result, this task is performed at a lower level. In this paper, we suggest a novel paradigm to handle these two concerns by robotics method framework. The suggested robotics framework is built on the essential premise that a sentence’s meaning is determined by its context and that sentence similarity may be determined by comparing the probabilities of forming two phrases given the same context. In an unsupervised way, the proposed approach can create high-quality, large-scale datasets with semantic similarity scores between two sentences, bridging the train-test gap to a great extent. Extensive testing shows that the proposed framework does better than existing baselines on a wide range of datasets.